Hydrodynamic performance of a multi-Oscillating Water Column (OWC) platform. (June 2020) - Zheng, Siming; Antonini, Alessandro; Zhang, Yongliang; Miles, Jon; Greaves, Deborah; Zhu, Guixun; Iglesias, Gregorio
Highlights: We propose a multi-oscillating water column (OWC) integrated platform. We develop a semi-analytical model to evaluate hydrodynamics of the platform. Wave power absorption and wave transmission of the multi-OWC platform are examined. Small-draft front wall and large-draft back wall are beneficial for power absorption. Platforms with inverse geometric constructions have the same transmission coefficient. Abstract: A rectangular barge consisting of multiple oscillating water columns (OWCs) is considered in this paper, hereinafter referred to as a multi–OWC platform. Each OWC chamber is enclosed by two partially submerged vertical walls and the deck of the platform. An incident wave produces oscillation of the water column in each OWC chamber and hence air is pumped by the internal water surface to flow through a Wells turbine installed at the chamber top. The effect of the turbine is characterised as a linear power take–off (PTO) system. A semi–analytical model based on linear potential flow theory and the eigen–function expansion method is developed to solve the wave radiation and diffraction problems of the multi–OWC platform. The hydrodynamic coefficients evaluated with direct and indirect methods of the model are shown to be in excellent agreement, and the energy conservation relationship of the multi–OWC platform is satisfied. The validated model is then applied to predict wave motion, dynamic air pressure, wave power extraction, and wave reflection and transmission coefficients of the multi–OWC platform. The effects of the PTO strategies, the number of chambers, the overall platform dimensions and the relative dimensions of adjacent chambers on wave power extraction and wave attenuation are investigated. A smaller–draft front wall and a larger–draft back wall are found to be beneficial for broadening the range of high–efficiency performance of the platform. The same wave transmission coefficient can be obtained by two multi–OWC platforms with inverse geometric constructions.